The Relative Valuation of Gold - Dirk G. Baur; Joscha Beckmann; Robert Czudaj (Chemnitz University of Technology, Faculty of Economics and Business Administration, 2017)
Gold is a globally traded asset and held in large quantities by investors and central banks. Since there is no established model to assess if the price of gold is overvalued or undervalued, we propose a relative valuation framework based on gold price ratios and focus on potential drivers of resulting misalignments. This idea is not confined to gold but offers the foundation for relative valuation of a broad range of different assets or asset classes in the spirit of Campbell and Shiller (2001). We analyze gold prices relative to commodity prices, consumer prices, stock prices, dividend and bond yields and find that the relative value of gold varies significantly over time indicating pronounced periods of mispricing of gold relative to other assets. An analysis of the factors which drive these variations demonstrates that inflation expectations and uncertainty have a strong influence on gold ratios while macroeconomic fundamentals are less important. More specifically, a boost in confidence decreases the relative price of gold while heightened uncertainty increases the relative price of gold which confirms the role of gold as a safe haven.
Keywords: G10; G15; 330; Gold; relative valuation; gold-silver ratio; safe haven; Bayesian econometrics